2009
DOI: 10.1071/wf06142
|View full text |Cite
|
Sign up to set email alerts
|

Wildland surface fire spread modelling, 1990 - 2007. 2: Empirical and quasi-empirical models

Abstract: In recent years, advances in computational power have led to an increase in attempts to model the behaviour of wildland fires and to simulate their spread across landscape. The present series of articles endeavours to comprehensively survey and précis all types of surface fire spread models developed during the period 1990-2007. The current paper surveys models of an empirical or quasi-empirical nature. These models are based on the statistical analysis of experimentally obtained data with or without some phys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
114
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 330 publications
(136 citation statements)
references
References 50 publications
1
114
0
1
Order By: Relevance
“…In addition, interactions of fuels and weather with local topography can greatly influence fire activity (Moritz et al 2010;Sharples et al 2012). Fire behaviour models incorporate information on fuels, topography and weather to predict fire spread (Sullivan 2009a(Sullivan , 2009b(Sullivan , 2009c. Comparison of fire behaviour model outcomes against real-world fires has indicated that models typically do not accurately predict fire progression (Papadopoulos and Pavlidou 2011;Finney et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, interactions of fuels and weather with local topography can greatly influence fire activity (Moritz et al 2010;Sharples et al 2012). Fire behaviour models incorporate information on fuels, topography and weather to predict fire spread (Sullivan 2009a(Sullivan , 2009b(Sullivan , 2009c. Comparison of fire behaviour model outcomes against real-world fires has indicated that models typically do not accurately predict fire progression (Papadopoulos and Pavlidou 2011;Finney et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…new mathematical models, to handle and understand better the spreading mechanism of the wildfires in forests, grasslands, and wheat fields -with wind, slope, varying fuel properties across the domain and in geographically complicated terrain, see for example the description of the wildfire simulator Prometheus in [14], the comparison of various simulators in [15,16], and the general surveys as in e.g. [17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the empirical tree mortality models may someday be replaced by physically based models (Butler and Dickinson 2010). Sullivan (2009aSullivan ( , 2009b) reviewed 39 models for surface fire spread developed from 1990 to 2007, and Alexander and Cruz (2012) list 20 fireline intensity-flame length relationships. Although research users may benefit from access to multiple models, fire managers will appreciate recommended models and methods.…”
Section: Future Needsmentioning
confidence: 99%